Análisis de la demanda eléctrica actual para la ampliación del sistema eléctrico en la planta procesadora de alimentos Genim S.A. del cantón Latacunga en el año 2017. - Palomo Gadvay, Diego Alexis (2017)
This research project aimed to carry out the analysis of the electrical system of the company Genim S.A .; The same one that has had an unplanned growth of the electrical demand, which is manifested in an unknown loadability of the current transformer, which has generated problems in the quality of voltage, power cuts by actuation of the electrical protections. This is why the objective is to determine the factors that currently produce low power quality in the electricity supply, by collecting information and obtaining measurements of the electrical system, this with the installation of a Fluke 435 load analyzer in the bus bars. General board, the same that reflected data of power, voltage, current, power factor. These measurements allowed to perform frequency histograms the same ones that were simulated in Etap software. Once the simulations were carried out, the electrical parameters of the industrial plant were known, resulting in the voltage levels being outside the 2% allowed by the regulation, in addition to that the transformer was within normal operating percentages At half-load with a value of 30.72 [KVA], because if the whole transformer was used, the transformer was overloaded, making it impossible to satisfy the demand of 92.25 [KVA]. Allows to satisfy the load to be implemented and according to the needs of the food processing plant to avoid the power cuts by overload and by voltage profiles.